The Effects of Insecurity on Socio-economic Development on Northern Kenya - Ogembo, Paul Okeyo (Indonesian Journal of Economics, Social, and Humanities, 2024)
Human insecurity of the Arid and Semi- Arid (ASALS) Northern Kenya is indeed a challenge towards realization of equal spatial-geographical development. Even though devolved systems of Government is in place towards near achievement of equal development through being disbursed for Equalization Funds on top financial yearly disbursement of funds to the counties in accordance to the constitution 2010 provisions on devolution, the region remains largely underdeveloped as compared to other regions in Kenya. Insecurity in this region are aggravated by practices such as cattle rustling in which sophisticated weapons like AK47 and M16 rifles are used by rustlers and terrorists more specifically Al-Shabaab especially in Mandera, Wajir, Garrisa and Lamu Counties. In addition, the Al-Shabaab use IED, hand propelled granades, landmines, matchettes amongst other lethal weapons. The scenario is that Civil servants more specifically non-locals in various sectors e.g. education, health, agriculture, security perceive the regions as being very insecure. The purpose of the study is to determine effects of insecurity on socio-economic development. Specific objectives were to establish: effects of insecurity on trade in Northern Kenya; to establish effects of insecurity on crop and livestock farming and to establish effects of insecurity education on health services. The study was underpinned by peaceful co-existence theory. The study established that there is a strong relationship between (in)security and socioeconomic development, that the insecurity in Northern Kenya has negatively affected trade, health services and livestock and livestock framing. Many civil servants flee the area because of the hostility that characterize the region. The findings have implications for security agencies drawn from the Ministry of Interior and Defense and County security apparatus to work closely with the local communities towards attainment of sustainable peace.